Improving the storage quality and suppressing off-flavor generation of winter jujube by precise micro-perforated MAP - Cui, Xinzhi; Ding, Yibing; Sun, Chanchan; Li, Xiulian; Yuan, Shuzhi; Guo, Fengjun; Zeng, Xiangquan; Fan, Xinguang; Sun, Shuyang (Frontiers in Plant Science, 2024)
Introduction Traditional modified atmosphere packaging (MAP) cannot meet the preservation requirements of winter jujube, and the high respiration rate characteristics of winter jujube will produce an atmosphere component with high CO2 concentration in traditional MAP. Micro-perforated MAP is suitable for the preservation of winter jujube due to its high permeability, which can effectively remove excess CO2 and supply O2. In this study, a microporous film preservation system that can be quickly applied to winter jujube was developed, namely PMP-MAP (precise micro-perforated modified atmosphere packaging). An experiment was designed to store winter jujube in PMP-MAP at 20°C and 2°C, respectively. The quality, aroma and antioxidant capacity, etc. of winter jujube at the storage time were determined. Methods In this study, the optimal micropore area required for microporous film packaging at different temperatures is first determined. To ensure the best perforation effect, the effects of various factors on perforation efficiency were studied. The gas composition within the package was predicted using the gas prediction equation to ensure that the gas composition of the perforated package achieved the desired target. Finally, storage experiments were designed to determine the quality index of winter jujube, including firmness, total soluble solids, titratable acid, reddening, and decay incidence. In addition, sensory evaluation, aroma and antioxidant capacity were also determined. Finally, the preservation effect of PMP-MAP for winter jujube was evaluated by combining the above indicators. Results and discussion At the end of storage, PMP-MAP reduced the respiration rate of winter jujube, which contributed to the preservation of high total soluble solids and titratable acid levels, and delayed the reddening and decay rate of winter jujube. In addition, PMP-MAP maintained the antioxidant capacity and flavor of winter jujube while inhibiting the occurrence of alcoholic fermentation and off-flavors. This can be attributed to the effective gas exchange facilitated by PMP-MAP, thereby preventing anaerobic stress and quality degradation. Therefore, the PMP-MAP approach is an efficient method for the storage of winter jujube.